2018
DOI: 10.1177/1479164118778850
|View full text |Cite
|
Sign up to set email alerts
|

Haemoglobin A1c variability as an independent correlate of atherosclerosis and cardiovascular disease in Chinese type 2 diabetes

Abstract: Objective: To examine the association between haemoglobin A1c variability and macrovascular complication in type 2 diabetes. Methods: We retrospectively enrolled 5278 diabetes patients with no history of cardiovascular disease and atherosclerosis by ultrasound at their first visit to the hospital from 1999 to 2010. Patients had a median of 4 haemoglobin A1c (range = 3-9) measurements during follow-up. Average haemoglobin A1c and haemoglobin A1c variability were calculated as intra-individual mean, standard dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…In patients with type 1 diabetes, HbA1c variability was found as an important risk factor for vascular complications such as cardiovascular diseases (CVDs) [8], microvascular diseases (MVDs) [8][9][10][11], and hospitalized hypoglycemia [12]. In patients with type 2 diabetes, although cumulative evidence shows the predictive role of HbA1c variability in the risks of hypoglycemia [12], CVDs [13][14][15][16][17][18][19][20] (such as subclinical left ventricular remodeling and dysfunction [21], reduced baroreflex sensitivity [22], and high thrombotic risk [23]), and allcause mortality [15][16][17][18][19][20][24][25][26][27][28][29][30], studies on MVDs [15,19,22,[31][32][33][34][35][36][37] are relatively limited and yield inconsistent results [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with type 1 diabetes, HbA1c variability was found as an important risk factor for vascular complications such as cardiovascular diseases (CVDs) [8], microvascular diseases (MVDs) [8][9][10][11], and hospitalized hypoglycemia [12]. In patients with type 2 diabetes, although cumulative evidence shows the predictive role of HbA1c variability in the risks of hypoglycemia [12], CVDs [13][14][15][16][17][18][19][20] (such as subclinical left ventricular remodeling and dysfunction [21], reduced baroreflex sensitivity [22], and high thrombotic risk [23]), and allcause mortality [15][16][17][18][19][20][24][25][26][27][28][29][30], studies on MVDs [15,19,22,[31][32][33][34][35][36][37] are relatively limited and yield inconsistent results [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…HbA1c variability can be measured as the following three metrics: (1) intra-individual standard deviation (HbA1c-SD), (2) coefficient of variation of HbA1c (HbA1c-CV), which is a normalized variability measure as the ratio of HbA1c-SD to intra-individual mean (HbA1c-mean), and (3) HbA1c variability score (HVS), which can be interpreted as the percentage of total HbA1c measures that vary by 0.5% (5.5 mmol/mol) [28]. However, there is lack of evidence for examining the comparative predictive abilities of various HbA1c variability measures for diabetic outcomes; most studies considered only one [13-15, 17, 24-28, 31-36] or two [16,29] variability measures. Although Tseng et al used three HbA1c variability measures (i.e., HbA1c-SD, HbA1c-CV, and HVS) to assess the role of mean HbA1c in the association between HbA1c variability and all-cause mortality, they did not further explore the comparative predictive abilities among these HbA1c measures [27].…”
Section: Introductionmentioning
confidence: 99%
“…Glycaemic variability is defined as the fluctuation of glucose homeostasis over a certain interval of time and is commonly evaluated by visit‐to‐visit HbA1c variability. Results from several studies have shown that visit‐to‐visit HbA1c variability may have a major impact on cardiovascular events and all‐cause mortality in patients with or without diabetes 6–8 . However, no studies have assessed the potential factors that could mediate the association between visit‐to‐visit HbA1c variability and the risk of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Glycemic variability includes short‐term glycemic variability such as postprandial hyperglycemia and long‐term glycemic variability as assessed by HbA 1c variability. Studies have shown that both short‐term and long‐term glycemic variability may be an important factor in the development of diabetes complications . CGM continuously captures patterns of hypoglycemia, hyperglycemia, and the short‐term glucose variability.…”
Section: Cgm Parametersmentioning
confidence: 99%